Preliminary Clinical Evaluation Using a Novel Bioengineered Wound Product to Treat Lower Extremity Ulcers. (March 2023) - Rodriguez, Isaac A.; Strombergsson, Axel; Weinstein, Robert; Maloney, Amanda; Hendrix, Christopher; Liden, Brock; Fridman, Robert
Diabetes mellitus affects hundreds of millions of people worldwide, each of which have up to a 25% risk of developing a diabetic foot ulcer (DFU) during their lifetime. With poor DFU healing rates using standard of care, advanced treatments are introduced to attempt to close the wound. The objective of this preliminary clinical evaluation was to evaluate lower extremity ulcers treated with a novel bioengineered wound product (BWP). The BWP, a solid absorbable and conformable sheet composed of gelatin, Manuka honey, and hydroxyapatite, was applied on 12 patients with lower extremity ulcers. The patients in this evaluation spanned across 4 sites and had complicated medical histories, including little to no progression of healing with standard of care or treatment with other biomaterials. The ulcers were treated with debridement, BWP placement, dressing, appropriate compression, and offloading as necessary. Weekly follow-up visits were recommended for evaluation, debridement, and BWP reapplication. Nine patients had the BWP applied to aid in full closure. These patients achieved 100% closure within 8 weeks, with a mean closure time of 4.1 weeks. At 4 weeks, the mean percent wound closure was 94%. Three patients had the BWP applied to aid in achieving a healthy wound bed for continued treatment (eg, splitthickness skin graft) and to cover (epithelialization over) an exposed tendon. In all 12 cases, no treatment site infections were observed. The results and observations from this preliminary clinical evaluation suggest that the BWP supports rapid wound closure, a predictor of complete healing for DFUs.